Physicochemical and Catechin Release Properties of Carboxymethyl Cellulose/κ-carrageenan’s Composite as Precursor of Active Green Packaging: A Preliminary Study - Khusna Santika Rahmasari; Wirasti; Vanesa Maharani; Eka Anidya Putri; Aulia Rahmadhani; Elsa Sabilla; Bayu Ishartono (Indonesian Journal of Chemical Studies, 2025)
The ongoing dependence on conventional petroleum-based plastic food packaging, and the increasing necessity to protect food quality against lipid oxidation, pose significant challenges that requires comprehensive scientific examinations. In response to these challenges, the development of green food packaging with biopolymer composites, enhanced with antioxidant substances, has become an urgent and promising area of investigation. This preliminary study demonstrated the novel fabrication of green food packaging films by solvent casting blended carboxymethyl cellulose (CMC) and κ-carrageenan (κ-Car) at specific ratios, resulting in a CMC/κ-Car biocomposites. Catechin (CAT), a model of phenolic-rich antioxidant, was incorporated into the CMC/κ-Car composite matrix to simulate the release of active compounds. The efficacy of the composite synthesis was assessed using spectrometric characterisation and physicochemical property evaluation. Infrared spectroscopy validated the successful synthesis and confirmation of the CMC/κ-Car composite, both in its original form and with CAT. Physicochemically, increasing κ-Car content improved tensile strength (TS), elongation at break (EAB), and water absorption capacity (WAC), with optimal performance at an 8:2 CMC/κ-Car ratio. The sustained release profile of CAT over a specific time interval revealed that the composite acted as a carrier matrix, with diffusion-driven release kinetics, as predicted by the Higuchi and Korsmeyer–Peppas equations. The findings of this preliminary study indicated that, the CMC/κ-Car composite, might have potential as a green food packaging material, improving shelf life and reducing lipid oxidation due to CAT's antioxidant properties.